2014
DOI: 10.1109/jcn.2014.000072
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and communications scheduling in WSNs using mixed integer linear programming

Abstract: We consider the problem of scheduling communications in Wireless Sensor Networks to ensure battery preservation through the use of sensors' sleeping mode. We propose a communication protocol in 1-hop WSNs and extend it to multi-hop WSNs thanks to a 1-hop clustering algorithm. Once the clustering is obtained, we propose to schedule communications in a virtual communication ring so as to avoid collisions. Since clusters are complete, only one sensor can speak or listen in a cluster at a time, and all sensors nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…But, like other centralized clustering approaches ECRA, ASPLR, and HEEMP relies on BS to compute the topology and causes a longer delay. Also, in clustering, there is no deterministic algorithm that can partition the network into balanced clusters . Moreover, in a sensor networks, there are multiple paths to reach a particular destination i.e.…”
Section: Related Workmentioning
confidence: 99%
“…But, like other centralized clustering approaches ECRA, ASPLR, and HEEMP relies on BS to compute the topology and causes a longer delay. Also, in clustering, there is no deterministic algorithm that can partition the network into balanced clusters . Moreover, in a sensor networks, there are multiple paths to reach a particular destination i.e.…”
Section: Related Workmentioning
confidence: 99%
“…However, this solution requires all clusters to be synchronized. Paper [21] investigates the communication scheduling that can maximize the parallel communication. Authors first use clique-clustering algorithm to partition the network into maximal cliques (clusters).…”
Section: Interference-free Strategymentioning
confidence: 99%
“…Even though only a few works are dedicated to interference-free, people do realize the importance of providing interference-free communication for cluster-based networks. Most of previous works introduce interference-free based on multiple access technologies or complex timeslot allocation methods for clustered WSNs [16]- [21], but the clusters themselves are not interference-free. This makes them inefficient, especially for large-scale WSNs.…”
Section: Introductionmentioning
confidence: 99%
“…Applications Technique [7] Interference-free localization Maximum flow [10], [32] Nodes deployment Quadratic Assignment [23] Network lifetime Set Cover Problem and variant [30] [43] Routing Graph Coloring Problem [33] Routing Voronoi based path searching [44], [47] Energy Saving Multipath [28] Network lifetime Linear programming [12] QoS Multipath [24] Minimizing Energy Binary Integer Linear Programming [27] Energy saving Mixed Integer Linear Programming [48] Routing and sink location Integer programming [29] Energy Minimum Dominant set [34] Routing Dominant Set [31] Node localization Integer linear programming [38] Node localization Mathematical programing [39] Node localization, network lifetime Linear Programming [41] Interference [7], [10], [27], [29], [32] [34], [41], [43], [45], [48], [49], [52], [58], [59], [62], [65] √ √ [12], [23], [24], [28], [33], [38], [39], [44], [46], …”
Section: Referencesmentioning
confidence: 99%
“…In such approaches, the node can reduce its energy so as to be able to reach only its best neighbors. In [27], authors suggested a mixed integer-programming model to solve the problem of scheduling communications in wireless sensor networks to ensure battery preservation through the use of the sleeping mode of sensors.…”
Section: Operations Research Techniques In Energy Savingmentioning
confidence: 99%